Extending working life and the management of change. Is the workplace ready for the ageing worker?. Issue 11 (5th July 2018) - Wainwright, David; Crawford, Joanne; Loretto, Wendy; Phillipson, Christopher; Robinson, Mark; Shepherd, Sue; Vickerstaff, Sarah; Weyman, Andrew
Abstract: Increasing longevity and the strain on state and occupational pensions have brought into question long-held assumptions about the age of retirement, and raised the prospect of a workplace populated by ageing workers. In the United Kingdom the default retirement age has gone, incremental increases in state pension age are being implemented and ageism has been added to workplace anti-discrimination laws. These changes are yet to bring about the anticipated transformation in workplace demographics, but it is coming, making it timely to ask if the workplace is ready for the ageing worker and how the extension of working life will be managed. We report findings from qualitative case studies of five large organisations located in the United Kingdom. Interviews and focus groups were conducted with employees, line managers, occupational health staff and human resources managers. Our findings reveal a high degree of uncertainty and ambivalence among workers and managers regarding the desirability and feasibility of extending working life; wide variations in how older workers are managed within workplaces; a gap between policies and practices; and evidence that while casualisation might be experienced negatively by younger workers, it may be viewed positively by financially secure older workers seeking flexibility. We conclude with a discussion of the challenges facing employers and policy makers in making the modern workplace fit for the ageing worker.